Analise de estimador de erro baseado em tecnica superconvergente de recuperação para o metodo dos elementos finitos - Max de Castro Magalhaes (1994)
This work analyses the Zienkiewicz-Zhu errorestimator (1992), implemented on a computational environment designed for the Finite Element applications which includes global r-h refinements. The estimator reaches an asymptotical convergence due to a new superconvergent recovery procedure (SPR) for gradients of the solution. Another recovery technique [Zuenkiewicz and Zhu, 1987] is also described and used for comparison in plane elasticity examples.